Novel Totally Laparoscopic Endolumenal Rectal Resection With Transanal Natural Orifice Specimen Extraction (NOSE) Without Rectal Stump Opening: A Modification of Our Recently Published Clean Surgical Technique in a Porcine Model. (June 2015) - Kvasha, Anton; Hadary, Amram; Biswas, Seema; Szvalb, Sergio; Willenz, Udi; Waksman, Igor
Our group has recently described a novel technique for clean endolumenal bowel resection, in which abdominal and transanal approaches were used. In the current study, 2 modifications of this procedure were tested for feasibility in a porcine model. A laparoscopic approach to the peritoneal cavity was employed in rectal mobilization; this was followed by a transanal rectorectal intussusception and pull-through (IPT). IPT was established in a stepwise fashion. First, the proximal margin of resection was attached to the shaft of the anvil of an end-to-end circular stapler with a ligature around the rectum. Second, this complex was pulled transanally to produce IPT. Once IPT was established, a second ligature was placed around the rectum approximating the proximal and distal resection margins. This was followed by a purse string suture through 2 bowel walls, encircling the shaft of the anvil just proximal to the ligatures. The specimen was resected and extracted by making a full-thickness incision through the 2 bowel walls distal to the previously placed purse string suture and ligatures. The anastomosis was achieved by applying the stapler. The technique was found to be feasible. Peritoneal samples, collected after transanal specimen extraction, did not demonstrate bacterial growth. Although, this is a novel and evolving procedure, its minimally invasive nature, as well as aseptic bowel manipulation during endolumenal rectal resection, has the potential to limit the complications associated with abdominal wall incision and surgical site infection.